Sodium diffuses from glass substrates through P1 lines and passivates defects in perovskite solar modules - Kosasih, Felix Utama (2023)
Most thin film photovoltaic modules are constructed on soda lime glass (SLG) substrates containing alkali oxides, such as Na2O. Na may diffuse from SLG into a module’s active layers through P1 lines, an area between a module’s constituent cells where the substrate-side charge transport layer (CTL) is in direct contact with SLG. Na diffusion from SLG is known to cause several important effects in II-VI and chalcogenide solar modules, but it has not been studied in perovskite solar modules (PSMs). In this work, we use complementary microscopy and spectroscopy techniques to show that Na diffusion occurs in the fabrication process of PSMs. Na diffuses vertically inside P1 lines and then laterally from P1 lines into the active area for up to 360 μm. We propose that this process is driven by the high temperatures the devices are exposed to during CTL and perovskite annealing. The diffused Na preferentially binds with Br, forming Br-poor, I-rich perovskite and a species rich in Na and Br (Na-Br) close to P1 lines. Na-Br passivates defect sites, reducing non-radiative recombination in the perovskite and boosting its luminescence by up to 5x. Na-Br is observed to be stable after 12 weeks of device storage, suggesting long-lasting effects of Na diffusion. Our results point to a potential avenue to increase PSM performance, but also highlights the possibility of unabated Na diffusion throughout a module’s lifetime, especially if accelerated by the electric field and elevated temperatures achievable during device operation.